Peran Fasilitator KB (Keluarga Berencana) dalam Pencegahan Pernikahan Usia Dini : Studi di Desa Pawindan, Kabupaten Ciamis - Revi Amelia Putri Nur; Wishal Pazril; Irfan Fauzi Badru Salam; Annisa Nuraeni; Nadya Sabda Galuh (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to find out the extent of the role of family planning extension facilitators in Pawindan Village, Ciamis district. The focus of the research is the role of facilitators in efforts to prevent early marriage. In this study, a descriptive qualitative method is used, namely research that tries to describe the object being researched based on the facts in the field, then in this study, data is collected from the DP2KBP3A and UPTD of the P5A Field of Ciamis District, interviews with informants who are considered to understand and understand this problem the most, as well as analysis of documents related to the problem of early marriage. The results of the study show that Facilitators have a very important role in supporting programs made by the Population Control, Family Planning, Women's Empowerment, and Child Protection (DPPKBP3A) Office. They act as a bridge between the government and the community, ensuring that the information and services provided are accessible and well understood by the public. The role of facilitators for the community to run the early marriage program has been implemented quite well in accordance with the needs of the community. This can be seen from the implementation of the program, the facilitator plays the role of providing solutions to the problems faced by the community. Although there are some people who think that facilitators have not been maximized in carrying out their roles. However, most of the community is helped in overcoming the problems faced